2021
DOI: 10.5194/ica-proc-4-78-2021
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Gold Mining Impact on the Vegetation of Itagunmodi-Igun Drainage Basin, Southwestern Nigeria from 1972–2011: A Remote Sensing

Abstract: Abstract. A GIS-based Normalized Differential Vegetation Index (NDVI) was analyzed using space-based data between 1972 and 2011 as Input data. The result of the NDVI using Landsat 7 ETM+ shows clearly that the values range from 0.19 to −0.31. Mountains and highlands of the Itagunmodi-Igun area revealed stressed vegetation cover between 0.11 to −0.31. The NDVI was also performed on Landsat imageries of four different epoch: 1972, 1986, 2000, and 2010. Results showed that vegetation index ranged from −0.105 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…In a comparable study which was analysed using the remote sensing approach, Oluwafemi et al (2021) showed that artisanal mining could cause land and vegetation degradation which might consequently result in loss of biodiversity, habitat displacement and ecological modification. Having collected time series data on vegetation, land use and biomass, the authors applied the GIS-based Normalized Differential Vegetation Index (NDVI) to analyse the space-based data ranging from 1972 to 2011.…”
Section: A Tour Of the Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a comparable study which was analysed using the remote sensing approach, Oluwafemi et al (2021) showed that artisanal mining could cause land and vegetation degradation which might consequently result in loss of biodiversity, habitat displacement and ecological modification. Having collected time series data on vegetation, land use and biomass, the authors applied the GIS-based Normalized Differential Vegetation Index (NDVI) to analyse the space-based data ranging from 1972 to 2011.…”
Section: A Tour Of the Related Literaturementioning
confidence: 99%
“…The results of the data analysis hinted that the NDVI values of the input data were in excess of their upper bands but within their lower bands. It therefore follows that mining activity represents push and pull factors to economic prosperity and environmental sustainability of the communities (Oluwafemi et al, 2021). Earlier, a GISfocused research by Atejioye and Odeyemi (2018) Given the lead poisoning outbreak in Zamfara, Nigeria in 2010, Bartrem et al (2022) investigated the vulnerabilities and complexities of challenges faced by gold mining villages in Zamfara.…”
Section: A Tour Of the Related Literaturementioning
confidence: 99%